ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN RESTO ONLINE DAPUR MOEZZAR DI TANGERANG - Darusman Aziz (Inovasi, 2021)
Moezzar's Kitchen Online Restaurant is one of the online restaurants engaged in the culinary field. Due to the increasingly fierce competition today, the management needs to review its marketing strategy from either the Market Strategy or the Marketing Mix Strategy. This study aims to determine the variables which are strengths, weaknesses, opportunities, threats and alternative strategies from SWOT Analysis and Marketing Mix Strategy. This research method is a descriptive qualitative research based on SWOT analysis. Research data is analyzed from the results of interviews and Focus Group Discussions in this study including Internal Key Informants, External Key Informants.. The results of the analysis show that the variables that become strengths are products according to restaurant standards, strong brand image, service with pick up service, strategic branch offices,. Then the threat is the number of competitors, competitors have advanced and complete technology, poor economic and political conditions. The marketing strategy reformulation that can be applied is the marketing mix strategy and the alternative strategy of SWOT matrix analysis. Based on the results of the study, it can be suggested to give special prices to consumers, be more aggressive in promotions, carry out training for employees, and improve service quality.Keywords: Marketing Mix, IFAS, EFAS